The Influence of Destination Personality, Destination Image and Customer Experience on Intention to Recommend at Trendy Coffee Cafe in Batam City - Ratih Anggraini; Erica Novianti Idris (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
This study was conducted to identify factors that influence intention to recommend interest towards trendy coffee cafe destinations in Batam City. This factor is important for trendy coffee cafe destination owners to understand how consumers influence their intention to recommend to other consumers. The object used in this research is trendy coffee cafe in Batam City. This type of research was conducted using quantitative methods. The data collection technique uses probability sampling techniques and purposive methods, then the data is collected and processed using SPSS IBM 25 software. The results of this study provide evidence that destination personality, destination image and good customer experience can significantly increase consumers' intention to recommend trendy coffee cafe to other consumers. Therefore, the independent variables partially and simultaneously have a positive and significant effect on the independent variable intention to recommend at trendy coffee cafe in Batam City